Creation Of The National Toponomic Geoinformation Base Of Uzbekistan - Shodiyev Sanjar Ruzikulovich; Jumayeva Mukhlisa Bakhshullayevna; Xamroqulova Sevara Farxodovna (Genius Journals, 2024)
This article presents a number of opinions on the creation of a database of geographic information systems, one of the areas of information and communication technologies. It also provides an overview of the sources of information support for these modern systems and aspects to which attention should be paid.
Keywords: information and communication technologies; geographic information systems; database of geographic information systems